Remote sensing in archaeology : an explicitly North American perspective - Johnson, Jay K. (University of Alabama Press, 2006)
NASA is composed of a vast and varied network of scientists across the academic spectrum involved in research and development programs that have wide application on planet Earth. This book, using case studies, reveals how the broad application of remote sensing and geophysical techniques is altering the usual conduct of dirt archaeology.